Lipopolysaccharide reduces gonadotrophin-releasing hormone (GnRH) gene expression: role of RFamide-related peptide-3 and kisspeptin - Lee, Chooi Yeng; Li, ShengYun; Li, Xiao Feng; Stalker, Daniel A. E.; Cooke, Claire; Shao, Bei; Clarke, Iain J. (Csiro Publishing, 2019)
RFamide-related peptide (RFRP)-3 reduces luteinising hormone (LH) secretion in rodents. Stress has been shown to upregulate the expression of the RFRP gene (Rfrp) with a concomitant reduction in LH secretion, but an effect on expression of the gonadotrophin-releasing hormone (GnRH) gene (Gnrh1) has not been shown. We hypothesised that lipopolysaccharide (LPS)-induced stress affects expression of Rfrp, the gene for kisspeptin (Kiss1) and/or Gnrh1, leading to suppression of LH levels in rats. Intracerebroventricular injections of RFRP-3 (0.1, 1, 5 nmol) or i.v. LPS (15gkg(-1)) reduced LH levels. Doses of 1 and 5 nmol RFRP-3 were then administered to analyse gene expression by in situ hybridisation. RFRP-3 (5 nmol) had no effect on Gnrh1 or Kiss1 expression. LPS stress reduced GnRH and Kiss1 expression, without affecting Rfrp1 expression. These data indicate that LPS stress directly or indirectly reduces Gnrh1 expression, but this is unlikely to be due to a change in Rfrp1 expression.
Keywords: hypothalamus; neuroendocrinology; neuropeptides; stress